Evaluation of Acute Pancreatitis in a Tertiary Centre: A Prospective Observational Study - Goel, Kanwar Singh; Goel, Nikhil; Goel, Sapna; Gupta, Tarun (Achievements and Challenges of Medicine and Medical Science Vol. 2, 2024)
Background: The etiology and clinical manifestations of pancreatitis have great variations. Acute pancreatitis is a common condition characterized by diverse etiologies, clinical presentations, and diagnostic findings. The disease may be mild or severe, may lead to multi-organ failures and death. The most common cause is biliary tract diseases. Other causes are alcohol consumption, post-ERCP (Endoscopic retrograde cholangiopancreatography), trauma, idiopathic and drugs, viral infections, genetic mutations and connective tissue disorders. Methods: This is a prospective observational study conducted at SGT Medical College, Budhera, Gurugram, Haryana, from January 2017 to June 2019 in 100 consecutive patients. The data was collected from case sheets and detailed clinical findings and investigations, treatment and complications from each patient. Analysis was made using software SPSS for Windows 7. The chi-square test and probability (p) value were used to establish the status of significance. Results: Most of the patients were from the age group 41-55 years. The most common etiology of acute pancreatitis was gallstone, followed by alcohol-induced cases. Other causes were idiopathic, post ERCP and trauma. Pain, distention abdomen, vomiting, fever and jaundice were presenting features. Serum amylase, serum lipase, USG abdomen and CECT (Contrast-Enhanced Computed Tomography) abdomen were diagnostic investigations. Complications included local and systemic. Mortality was 7%. The results of the study are quite comfortable and it is probably due to meticulous care at all steps. A local complication rate of 16% was achieved in the study. Conclusions: Acute pancreatitis is mild in most of the cases and recovery is good. Severe cases should be meticulously treated as mortality rates are higher. They should be treated in the ICU under the guidance of an intensivist. This study results show that patients with severe diseases should be meticulously monitored clinically, biochemically, hemodynamically and radiologically.